2021
DOI: 10.1101/2021.01.04.20248897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-2 and IFN-γ are biomarkers of SARS-CoV-2 specific cellular response in whole blood stimulation assays

Abstract: A proper description of the immune response to SARS-CoV-2 will be critical for the assessment of protection elicited after both infection and vaccination. Uncoupled T and B cell responses have been described in acute and convalescent patients and exposed individuals. We assessed the potential usefulness of whole blood stimulation assays to identify functional cellular immune responses to SARS-CoV-2. Blood from COVID-19 recovered individuals (5 months after infection) and negative subjects was stimulated for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Next, we attempted to understand which SARS-CoV-2 proteins regulate interferon and interleukin production through host protein interactions and the effects of mutation in these SARS-CoV-2 proteins in those interactions. From the literature, we found the N protein of SARS-CoV-2 induces IFN-γ expression [17,18], ORF8 regulates IL-17 signaling [20], and IFN-γ mediated antiviral responses [23], and M protein inhibits expression IFN-λ1 [24]. We modelled the mutant ORF8, M, and N proteins of the Omicron, Delta, and Gamma variants compared with the original Wuhan sequence.…”
Section: Sars-cov-2 M N and Orf8 Protein Variants May Differentially ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we attempted to understand which SARS-CoV-2 proteins regulate interferon and interleukin production through host protein interactions and the effects of mutation in these SARS-CoV-2 proteins in those interactions. From the literature, we found the N protein of SARS-CoV-2 induces IFN-γ expression [17,18], ORF8 regulates IL-17 signaling [20], and IFN-γ mediated antiviral responses [23], and M protein inhibits expression IFN-λ1 [24]. We modelled the mutant ORF8, M, and N proteins of the Omicron, Delta, and Gamma variants compared with the original Wuhan sequence.…”
Section: Sars-cov-2 M N and Orf8 Protein Variants May Differentially ...mentioning
confidence: 99%
“…On the other hand, the S and Nucleocapsid (N) proteins of SARS-CoV-2 induce antiinflammatory IFN-γ production in the host upon infection [17,18]. Further, the nonstructural protein-1 (NSP1) and N protein block the type I interferon (IFN-β) induction in the host and attenuate antiviral immune responses [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our results also highlighted a limited release of IL-4 in the mice treated with the middle dose of RAZI-COV PARS candidate vaccine, suggesting the low activation of Th2 immune response. IL-2 is a growth factor for production of memory T cells and the cellular expansion of specific T cells ( 69 ). Intracellular staining reported that both CD4+T and CD8+T cells are the origins of this cytokine but the main generation of this cytokine carried out through CD4+T cells ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…42 Recent research has explored the elevated levels of IL-2 found in mild or asymptomatic COVID-19 cases and highlighted the latent use of IL-2 among cytokines as prognostic biomarkers for pandemic SARS-CoV-2 infection and degree of immunity aer vaccination. 43,44 Though our current LOD does not satisfy the required level (below 10 pg mL À1 ) of IL-2 detection to diagnose COVID-19 infection; an improved suitable nanomaterial-assisted assay 15 could meet that diagnostic demand.…”
Section: Immunoassay Applicationsmentioning
confidence: 93%
“…Additionally, we demonstrated the effectiveness of the scheme by performing on-device immunoassay to detect human interleukin 2 (IL-2), which is a potential biomarker for testing/diagnosis of infections, immune response, cytotoxicity, and lymphocyte transformation. 33,[42][43][44] We envision this simple microuidic approach as a valuable tool for enabling many easy-to-perform instantaneous bioassays or rapid POC tests during emergencies or in situations where access to resources is constrained.…”
Section: Introductionmentioning
confidence: 99%